Type I collagen gene knockdown by RNA interference. - Li, Meng. (2009)
Ever since synovium-derived mesenchymal stem cells (SMSCs) were first isolated from human synovial membrane tissues in 2001, they have been widely investigated for potential use in musculoskeletal therapy. SMSCs have superiority in chondrogenesis, which makes them good source of cell for cartilage regeneration. It is crucial to inhibit the Collagen I expression of SMSC because Collagen I brings serious problems to cartilage regeneration. In this project, we try to silence the Collagen I expression of SMSCs by antisense technology. Recombinant adenovirus encoding shRNA which targets Collagen I were constructed and Collagen I knock down has been achieved in testing cells such as fibroblasts and osteoblasts.